PENYIMPANGAN SOSIAL PADA KALANGAN REMAJA DI GOR PERAHU KAJANG KECAMATAN KAYUAGUNG KABUPATEN OGAN KOMERING ILIR - Tiara Juniarti; Yoyok Hendarso; Safira Soraida (Department of Sociology, Faculty of Social and Political Sciences, Sriwijaya University, 2021)
Social deviation is an act, and an action taken by a person or group of people consciously or unconsciously that violates the values and norms in the local community. This study aims to analyze the forms of social deviation among adolescents, and to analyze the factors that cause social deviations among adolescents in the Perahu Kajang Sports Center, Kayuagung District, Ogan Komering Ilir Regency. This study uses the concept of social deviation by Kartopoetra. This study uses a qualitative descriptive research method with 8 main informants and 3 supporting informants. Data collection techniques in this study are observation, interviews, and documentation. The researcher also acts as a semi participantory , namely by establishing friendships with research informants such as inviting them to hang out together, asking to eat together, exchanging WhatsApp, and dressing like teenagers who do social deviations. The results of the study are about the forms of social deviation among adolescents, and the factors that cause social deviations among adolescents in the Perahu Kajang Sports Center. The forms of social deviation that occur in the form of negative social deviations and individual social deviations. Negative social deviations are primary deviations such as hanging out, and taking selfies or taking pictures. Meanwhile, secondary deviations such as dating include hugs, kisses, kisses, and even husband and wife relationships. Individual social deviation in the form of liquor, and wild races. Factors of social deviation among adolescents in the Perahu Kajang Sports Center are divided into internal factors and external factors. Internal factors include a relatively young age, curiosity, and a deviant learning process. Meanwhile, external factors include family factors, and promiscuity.